Harnessing the power of continuous auditing : developing and implementing a practical methodology - Mainardi, Robert L. , 1964- (Wiley corporate F&A series, 2011)
"In order to ensure that the structure surrounding the operational environment is sound, auditors and controllers need guidance on how to take continuous auditing from concept to reality. Drawing on the author?s two decades of auditing experience, this book is a "how to" for building, marketing, and managing a continuous auditing process for companies. It provides step-by-step instruction regarding continuous auditing objectives, a handbook for execution, and tips for achieving better SOX work. Using documented, proven techniques, Continuous Auditing is an essential text for those involved in regulating financial information"